Learning from accidents - Kletz, Trevor A. (Oxford ; Boston : Gulf Professional, 2001)
Review of previous edition: "Trevor Kletz's book makes an invaluable contribution to the systematic, professional and scientific approach to accident investigation". The Chemical Engineer Fully revised and updated, the third edition of Learning from Accidents provides more information on accident investigation, including coverage of accidents involving liquefied gases, building collapse and other incidents that have occurred because faults were invisible (e.g. underground pipelines). By analysing accidents that have occurred Trevor Kletz shows how we can learn and thus be better able to prevent accidents happening again. Looking at a wide range of incidents, covering the process industries, nuclear industry and transportation, he analyses each accident in a practical and non-theoretical fashion and summarises each with a chain of events showing the prevention and mitigation which could have occurred at every stage. At all times Learning from Accidents, 3rd Edition emphasises cause and prevention rather than human interest or cleaning up the mess. Anyone involved in accident investigation and reporting of whatever sort and all those who work in industry, whether in design, operations or loss prevention will find this book full of invaluable guidance and advice. Completely up-dated. Shows, by analysing accidents that have occurred, how we can learn from them, and prevent the same accidents happening again.
Introduction; Two simple incidents; Protective system failure; Poor procedures and poor management; A gas leak and explosion -- The hazards of insularity; A liquid leak and fire -- The hazards of amateurism; Another tank explosion -- The hazards of optional extras; Flixborough; Seveso; Bhopal; Three Mile Island; Chernobyl; Aberfan; Missing recommendations; Three weeks in a works; Some pipe failures; Piper Alpha; The King's Cross underground railway station fire; Clapham Junction -- Every sort of human error; Herald of Free Enterprise; Some aviation accidents; Invisable hazards; Signals passed at danger; Longford: The hazards of following fashions; The Gresford colliery explosion; Green intention, red result; Looking beyond violations; Keeping an open mind; Secondhand software: The Therac story. Conclusions; Epilogue: Myths on incident investigations -- widely held beliefs that are not wholly true.
Includes bibliographical references and index.
Keywords: Chemical industry -- Accidents; Industrial accidents; Industrial accidents -- Investigation; Electronic books